The impact of Digital Transformation on Business Strategy Development in the 4.0 Industry Era - Tristianto, Chrisantus; Zein, Afrizal (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2025)
Digital transformation has become a key driver in reshaping business strategies in the era of Industry 4.0. Rapid technological advancements, such as artificial intelligence, the Internet of Things (IoT), and big data analytics, have forced companies to adapt their business models to remain competitive. This paper aims to explore the impact of digital transformation on business strategy development amid the ongoing industrial revolution. By applying management theories and case studies from various sectors, the research highlights how digitalization influences the way companies design and implement their strategies. The study utilizes a qualitative research method, including in-depth interviews and content analysis, to gather insights from industry experts and business leaders. The findings indicate that organizations that successfully adopt digital technologies are more agile, capable of accessing real-time data, and able to improve operational efficiency and customer experience. Additionally, challenges such as cybersecurity threats and the digital skills gap are also discussed. Overall, the study reveals that to remain relevant in an increasingly connected and digital marketplace, companies must integrate technology into their business strategies holistically. Therefore, digital transformation is not just a technological initiative, but a critical factor in the development of business strategies in the Industry 4.0 era.